Odpowiedź :
Odpowiedź:
e)
1,3x - 0,4y - (0,2x + 0,5y) - (1,7 - 0,2x) = 1,3x - 0,4y - 0,2x - 0,5y - 1,7 + 0,2x = 1,3x - 0,9y - 1,7
f)
0,3x - (5 + 0, 7y) - 0,9 - 0, 1 x + (x − 0,1 ) = 0,3x - 5 - 0,7y - 0,9 - 0,1x + x - 0,1 = 1,2x - 0,7y - 6
g)
7a - (2a +3b + ab) + 2a -3ab) = 7a - 2a - 3b - ab + 2a - 3ab = 7a - 3b - 4ab
h)
4xy + (-2x - 3y) - (-5x + y - 5xy) = 4xy - 2x - 3y + 5x - y + 5xy = 3x + 9xy - 4y
i)
6m - (2m² - n) + (3m - 2n - 5m²) = 6m - 2m² + n + 3m - 2n - 5m² =
= -7m² + 9m - n
j)
-2t - (3t - t²) - 5s + 4t) - (2t² - s) = -2t - 3t + t² - 5s + 4t - 2t² + s = -t² - t - 4s
Szczegółowe wyjaśnienie: